Association between high on-treatment platelet reactivity to clopidogrel and hepatosteatosis in patients undergoing elective stent implantation - Yalçın Velibey; Ahmet İlker Tekkeşin; Hakan Barutca; Özlem Yıldırımtürk; Emrah Bozbeyoğlu; Yasin Çakıllı; Özge Güzelburç; Seviye Bora Şişman; Göksel Çinier; Sinan Şahin; Ahmet Taha Alper (KARE Publishing, 2018)
Objective: The present study is an investigation of the association between high on-treatment platelet reactivity to clopidogrel (HTPRC) and hepatosteatosis in patients who had elective stent implantation due to coronary artery disease. Methods: A total of 190 consecutive patients who underwent an elective coronary stent implantation due to coronary artery disease were prospectively enrolled in the study. Eligible patients were given a 300 mg loading dose of clopidogrel before percutaneous coronary intervention. All of the patients underwent an ultrasound assessment for fatty liver. The patients were divided into 2 groups according to the detection of HTPRC: patients with HTPRC and patients without HTPRC. Results: HTPRC was present in 54.2% (103 of 190 patients) of the total study population. The age and body mass index data were similar between the 2 groups. In all, 111 (58.6%) patients had hepatosteatosis. The HTPRC ratio was statistically higher in female patients (p=0.032). Hepatosteatosis was significantly greater in patients with HTPRC (p<0.001); 84 (81.6%) patients with HTPRC had hepatosteatosis (p=0.001). There was also a statistically significant association between the hepatosteatosis grade and HTPRC (p<0.001). The percentage of HTPRC was greater in patients with ≥grade 2 hepatosteatosis than grade 1 (p<0.001). Logistic regression analysis indicated that hepatosteatosis (odds ratio: 9.403, 95% confidence interval: 4.519-19.566; p<0.001), fasting blood glucose, and hypertension were independent predictors of HTPRC. Conclusion: To the best of our knowledge, this is the first study to demonstrate a relationship between hepatosteatosis and HTPRC.